(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Among many mosquito control approaches, the use of mosquito coil is popular because of its cost effectiveness and ease of use. But along with repelling mosquitoes, the burning of mosquito coils can cause severe health hazard. In mosquito coils, pyrethrin, allethrin, d-allethrin etc. are typically used as active ingredients. In this study, it was found that mosquito coil is used mostly (51%) in rural area and most of the rural people (64.7%) believed it to be beneficial as mosquito repellent as well as they are not so aware of the harmful effects of the mosquito coil (25%). Due to mosquito coil burning, the participants feel many such complications like suffocation (32.3%), eye irritation (29.2%), sneezing (13.1%) but they do not take any special measure or treatment to protect them. Rather, they mostly place the coil away from them (50%) to protect themselves after being exposed to those complications. These findings have raised a question, ― which one is more harmful: Mosquito or mosquito coil? Besides, most of the people even don’t know about the dangerous effects of mosquito coils. Although mosquito net is the most effective way to repel mosquito, 69% people do not use mosquito net due to laziness. Extensive research regarding alternative mosquito repelling strategy and safe use of mosquito coil is urgently needed in the context of countries like Bangladesh. Bangladesh Pharmaceutical Journal 27(1): 92-102, 2024 (January)